Web-Based Community Satisfaction System Survey (Case Study in Regional Revenue Management Unit Holy District) - Muhammad Aldy Firmansyah; Ahmad Jazuli (PT FORMOSA CENDEKIA GLOBAL, 2023)
As public service providers, officials have obligations and responsibilities responsible for the quality of services provided to the community. People who receive services from service providers should have a right and authority to provide an opinion or assessment of the service they have received. This research aims to design and build a Survey System Web Based Community Satisfaction (Case Study in Management Unit Kudus Regency Regional Revenue). This website was built with language HTML, PHP, CSS, Java Script and database programming uses MySQL, where this Web Application has 3 access rights, namely admin, surveyor, and visitors/respondents. This survey questionnaire application is integrated with the base data, by utilizing the MySql database, data processing and creation reporting becomes easier. Data collection with survey questionnaires can be more effective and efficient, as well produce relevant information.